IMPLEMENTASI SEARCH ENGINE OPTIMIZATION (SEO) ON PAGE PADA WEB UMKM BATIK DAN HANDICRAFT - Sutanto, Felix Andreas; ., Sri Mulyani (Proceeding SENDI_U, 2015)
Most Batik and Handicraft UMKM experiencing difficulties in marketing their products. The solution given wasto create a website, but to optimize the website also required certain techniques. Unfortunately some batik andhandicraft UMKM do not understand it. Therefore, this study will implement the techniques that batik andhandicraft UMKM website recognized by the search engines. This research will be implemented ContentManagement System (CMS) and Search Engine Optimization (SEO) using On Page techniques. On PageTechniques can be done such as by creating a template that is SEO friendly and fast when accessed, put metatags and keywords. Survey and analysis of keywords on batik and handicraft will be done so that each productcan occupy the top rank in Google search. Results from this study is the website Batik and Handicraft whichimplements SEO On Page in an easy way. The use of Content Management System is expected to help webmanagers of UMKM to promote their products and probably increase sales of UMKM products. Sebagian besarUMKM Batik dan Handicraft mengalami kesulitan dalam memasarkan produknya. Solusi yang diberikan adalahmembuat website, namun untuk mengoptimalkan website juga diperlukan teknik tertentu agar web dikenalorang. Namun sayangnya beberapa UMKM batik dan handicraft tidak memahami hal tersebut. Oleh karena itu,penelitian ini akan mengimplementasikan teknik agar website UMKM batik dan handicraft dikenal oleh mesinpencari. Penelitian ini akan mengimplementasikan website berbasis Content Management System (CMS) danSearch Engine Optimization (SEO) menggunakan teknik On Page. Teknik On Page dapat dilakukan diantaranyadengan membuat template yang SEO friendly dan cepat saat diakses, memasang meta tag dan keyword. Surveydan analisa keyword tentang batik dan handicraft akan dilakukan agar setiap produk dapat menempati rangkingteratas dalam pencarian Google. Hasil dari penelitian ini adalah website UMKM Batik dan Handicraft yangmengimplementasikan SEO On Page dengan cara yang mudah. Penggunaan Content Management Systemdiharapkan dapat membantu pengelola web UMKM untuk mempromosikan produknya dan berakibat padapeningkatan penjualan produk UMKM tersebut.Keywords: web, mesin pencari, seo, search engine optimization, on page, umkm, batik, handicraft, google